Powerful Representative of Uzbek Literature of The Period of National Renaisence Zokirjon Holmuhammad Ogli Furkat (1859-1909 y.y.) - Kushbakova Barno Batirkulovna; Abdug’aniyeva Nilufar Botirqul qizi (Research Parks Publishing LLC, 2021)
This article describes the life and work of Zokirjon Kholmuhammad oglu Furkat, his work in the field of spirituality and enlightenment, the importance of his works and ghazals